HOW IS QUALITY EDUCATION ACHIEVED? - Hojieva Rukhsatbegim Tuymurod kizi (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
Education is the process of imparting knowledge, skills, and abilities and is the main means of preparing a person for life and work. In the process of education, information is obtained and education is carried out. Education means teaching in a narrow sense. But it means not only the process of teaching in different types of educational institutions but also the process of providing information in the family, production, and other areas. This article provides information on effective ways to improve the quality of education and achieve quality education, which is considered the most urgent need of today's era. Various facts and examples are also provided to convey the information perfectly.